2013
DOI: 10.1175/jas-d-13-053.1
|View full text |Cite
|
Sign up to set email alerts
|

Water Budget and Precipitation Efficiency of Typhoon Morakot (2009)

Abstract: In this study, the Weather Research and Forecasting model, version 3.2, with the finest grid size of 1 km is used to explicitly simulate Typhoon Morakot (2009), which dumped rainfall of more than 2600 mm in 3 days on Taiwan. The model reasonably reproduced the track, the organization, the sizes of the eye and eyewall, and the characteristics of major convective cells in outer rainbands. The horizontal rainfall distribution and local rainfall maximum in the southwestern portion of the Central Mountain Range (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…The daily rainfall distribution over Taiwan on 8 August shows the highest accumulation along the southern CMR and in southwestern Taiwan (Figure (c)). The precipitation efficiency of Morakot over the CMR was enhanced to more than 95% due to strong orographic lifting (Huang and Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…The daily rainfall distribution over Taiwan on 8 August shows the highest accumulation along the southern CMR and in southwestern Taiwan (Figure (c)). The precipitation efficiency of Morakot over the CMR was enhanced to more than 95% due to strong orographic lifting (Huang and Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al . [] analyzed water budget and precipitation efficiency of Typhoon Morakot (2009) and showed that condensation and ice deposition caused the high precipitation efficiency over the Central Mountain Ranges, producing tremendous rainfall in southwestern Taiwan. Fritz and Wang [] investigated the evolution of water budgets from tropical wave stage to tropical cyclone stage using a high‐resolution model.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [2011] analyzed water budget of Typhoon Nari (2001) with Weather Researching and Forecasting (WRF) Model and revealed that Taiwan's steep terrain enhanced precipitation efficiency and surface rain rate by significantly strengthening secondary circulations and producing stronger vapor import at low levels. Huang et al [2014] analyzed water budget and precipitation efficiency of Typhoon Morakot (2009) and showed that condensation and ice deposition caused the high precipitation efficiency over the Central Mountain Ranges, producing tremendous rainfall in southwestern Taiwan. Fritz and Wang [2014] investigated the evolution of water budgets from tropical wave stage to tropical cyclone stage using a high-resolution model.…”
Section: Introductionmentioning
confidence: 99%
“…One was aligned north-south (N-S) near 120.7 • E along the windward slopes of the southern Central Mountain Range (Figs. 2a-d and 3a, Wang et al, 2012), produced through forced uplift of moisture-laden air by the steep topography at high precipitation efficiency (Yu and Cheng, 2013;Huang et al, 2014). On the other hand, the second type of rainbands was nearly E-W oriented and parallel to the flow.…”
Section: Typhoon Morakot and Back-building Rainbandsmentioning
confidence: 99%